STUDY OF SERUM MAGNESIUM AND OTHER ELECTROLYTES IN PATIENTS OF ACUTE SEVERE ASTHMA RECEIVING PARENTERAL ΒETA ADERENERGIC AGONISTS - VAMSI KRISHNA CHITTIMOJU; SUJATHA PASULA (International Journal of Pharma and Bio Sciences, 2013)
Asthma is a very common disease with immense social impact. Its acute exacerbations are commonly treated with salbutamol. The study intends to determine the magnitude of changes in serum magnesium, potassium, phosphate and calcium during treatment of acute severe asthma with parenteral salbutamol. This is a prospective study comprising of 80 patients who presented to casualty with symptoms of acute severe asthma and met the inclusion criteria. Baseline serum magnesium, potassium, phosphate and calcium levels were measured. Nebulised salbutamol was administered every thirty minutes till symptoms subsided. After 80 minutes, repeat serum levels of electrolytes were determined. Treatment followed with Parenteral salbutamol administration during the emergency treatment of acute severe asthma is associated with statistically significant decreases in serum magnesium, potassium, and phosphate levels. It is also associated with decrease in serum calcium levels, although the decrease was not statistically significant. The mechanism and clinical significance of these findings are currently unknown and warrant further study.